Biological Assessment of a 18F-Labeled Sulforhodamine 101 in a Mouse Model of Alzheimer’s Disease as a Potential Astrocytosis Marker - Kreimerman, Ingrid; Reyes, Ana Laura; Paolino, Andrea; Pardo, Tania; Porcal, Williams; Ibarra, Manuel; Oliver, Patricia; Savio, Eduardo; Engler, Henry (Frontiers in Neuroscience, 2019)
Neurodegenerative diseases have mainly been associated with neuronal death. Recent investigations have shown that astroglia may modulate neuroinflammation in the early and late stages of the disease. [11C]Deuterodeprenyl ([11C]DED) is a tracer that has been used for reactive astrocyte detection in Alzheimer’s disease, Creutzfeldt–Jakob disease and amyotrophic lateral sclerosis, among others, with some limitations. To develop a new radiotracer for detecting astrocytosis and overcoming associated difficulties, we recently reported the synthesis of a sulfonamide derivative of Sulforhodamine 101 (SR101), labelled with 18F, namely SR101 N-(3-[18F]Fluoropropyl) sulfonamide ([18F]2B-SRF101). The red fluorescent dye SR101 has been used as a specific marker of astroglia in the neocortex of rodents using in vivo models. In the present work we performed a biological characterisation of the new tracer including biodistribution and micro-PET/computed tomography (CT) images. PET/CT studies with [11C]DED were also done to compare with [18F]2B-SRF101 in order to assess its potential as an astrocyte marker. Biodistribution studies with [18F]2B-SRF101 were carried out in C57BL6J black and transgenic (3xTg) mice. A hepatointestinal metabolization as well as the pharmacokinetic profile were determined, showing appropriate characteristics to become a PET diagnostic agent. Dynamic PET/CT studies were carried out with [18F]2B-SRF101 and [11C]DED to evaluate the distribution of both tracers in the brain. A significant difference in [18F]2B-SRF101 uptake was especially observed in the cortex and hippocampus, and it was higher in 3xTg mice than it was in the control group. These results suggested that [18F]2B-SRF101 is a promising candidate for more extensive evaluation as an astrocyte tracer. The difference observed for [18F]2B-SRF101 was not found in the case of [11C]DED. The comparative studies between [18F]2B-SRF101 and [11C]DED suggest that both tracers have different roles as astrocytosis markers in this animal model, and could provide different and complementary information at the same time. In this way, by means of a multitracer approach, useful information could be obtained for the staging of the disease.